Efeito anticatabólico dos derivados de xantina no metabolismo de proteínas em músculos esqueléticos de ratos sépticos: um estudo de microdiálise - Lira, Eduardo Carvalho (2006)
Introduction: The aim of the present study was to estimate the anticatabolic effect of xanthine derivatives on skeletal muscle protein metabolism from septic rats by using microdialysis. Methods: Sepsis was induced by cecal ligation and puncture (CLP). After 3, 6 and 10 hours of surgery, male Wistar rats (~250g) were anesthetized with thionembutal sodium (50mg/Kg body weight i.p.) and placed on heating pads to maintain adequate temperature (37oC). Microdialysis probe was inserted in the anterior tibial muscle and an equilibration period of 30 minutes was allowed. After connecting the catheter inlet to a microinjection pump, the system was perfused with 0,5% bovine serum albumin, 50 μM tyrosine and 1 mmol/l glucose in isotonic saline at a rate of 1.0 μl/min. Samples of the skeletal muscle interstitial fluid and arterial plasma from carotid artery were collected after 90 minutes of experiment and tyrosine was measured by fluorescence. The interstitial tyrosine concentration was estimated from the dialysate concentration. To calibrate catheters in vivo the internal reference calibration technique was used. The muscle blood flow was estimated by ethanol technique. Overall proteolysis was investigated in extensor digitorus longus (EDL) muscles from sham-operated and 3-hour septic rats (~70g) incubated in the presence or not of IBMX (1mM). Results: In sham-operated and septic rats, skeletal muscle interstitial tyrosine levels (μM) were significantly higher than arterial plasma tyrosine. Three-hour septic rats showed a 33% decrease in muscle blood flow and a 128% increase in the concentration of tyrosine in skeletal muscle interstitial (235 ± 16, n=10), when compared to sham-operated rats (95,5 ± 5,5, n=10). Interstitial (I) minus arterial (A) plasma tyrosine concentrations difference was also significantly increased after 3 hours of sepsis (117 ± 7 vs. 31 ± 6 in sham-operated, n=10). Pentoxifylline (PTX; 50mg/Kg body weigh, e.v.) treatment, during 1 hour immediately after CLP, reduced in 25% and 50% the interstitial tyrosine concentration and I-A difference, respectively. In situ isobutylmethylxanthine (IBMX; 1mM), but not PTX, reduced the interstitial tyrosine concentration (30-46%) and I-A difference (43-48%) in both groups. The increase of proteolysis induced by sepsis in EDL muscles was abolished by in vitro addition of IBMX (1mM). Conclusions: The data show that: (1) microdialysis is a perfectly adapted tool to investigate in vivo regulation of muscle protein metabolism during acute catabolic states; (2) the catabolic effect of sepsis on rat skeletal muscle protein metabolism in vivo can be observed 3 hours after CLP; (3) the xanthine derivatives reduce the muscle protein catabolism induced by sepsis in rats.